Some rule ordering problems in Malay phonology - Farid M. Onn., (Universiti Kebangsaan Malaysia, 1977)
This paper discusses one of the main issues in current phonological theory, namely rule ordering. The standard theory of generative phonology which provides for the ordered application of phonological rules in one fixed linear order, is considered too strong; however, other proposed hypotheses, such as "Local Ordering", "Unordered Rule Hypothesis" and "Direct Mapping Hypothesis" are equally untenable. In this paper evidence is given in favour of incorporating a generalized version of derivational history into phonological theory. Specifically, it is argued that unless we make use of global constraints that can refer to derivationally earlier forms of input strings, then the process of vowel nasalization in Ulu Muar Malay cannot be explained without recourse to extrinsic rule ordering statements or other arbitrary devices.